2021
DOI: 10.3390/coatings11070742
|View full text |Cite
|
Sign up to set email alerts
|

The Protection, Challenge, and Prospect of Anti-Oxidation Coating on the Surface of Niobium Alloy

Abstract: Niobium (Nb)-based alloys have been extensively used in the aerospace field owing to their excellent high-temperature mechanical properties. However, the inferior oxidation resistance severely limits the application of Nb-based alloys in a high-temperature, oxygen-enriched environment. Related scholars have extensively studied the oxidation protection of niobium alloy and pointed out that surface coating technology is ideal for solving this problem. Based on the different preparation methods of Nb-based alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In the preparation process of coating, adding an appropriate amount of beneficial components (Al, B, YSZ, ZrO 2 , Al 2 O 3 , SiC, MoB, etc.) can significantly improve the oxidation resistance and mechanical properties of the silicide coatings [44][45][46][47][48][49]. The main reaction equations involved in the above process are shown in Figure 2g.…”
Section: Microstructure and Growth Mechanism Of Hapc Coatingsmentioning
confidence: 99%
“…In the preparation process of coating, adding an appropriate amount of beneficial components (Al, B, YSZ, ZrO 2 , Al 2 O 3 , SiC, MoB, etc.) can significantly improve the oxidation resistance and mechanical properties of the silicide coatings [44][45][46][47][48][49]. The main reaction equations involved in the above process are shown in Figure 2g.…”
Section: Microstructure and Growth Mechanism Of Hapc Coatingsmentioning
confidence: 99%
“…It's well known that the increase of oxide layer thickness is primarily caused by the internal diffusion of O 2 [49][50][51][52], and studies have shown that alloying with active elements can effectively reduce the internal diffusion rate of O 2 [53][54][55]. For example, appropriate adding rare earth elements, on the one hand, can separate oxygen atoms at the metal-oxide interfaces and oxide scale grain boundaries and react with O 2 , thus hindering the diffusion of O 2 [56][57][58][59].…”
Section: Effects Of Rare Earth Elements On Oxidation Behaviormentioning
confidence: 99%
“…Metallic UHTMs currently under development are refractory metal (RM) intermetallic composites (ICs) (i.e., RMICs), RM high entropy alloys (RHEAs) and RM complex concentrated alloys (RC-CAs) [1,[3][4][5][6][7] (see Appendix A for abbreviations). Like the Ni-based superalloys, in an HPT the new metallic UHTMs will be part of a material system that consists of a metallic UHTM substrate plus environmental coating, most likely of the bond coat/thermally grown oxide/top coat type [2,[8][9][10][11][12][13][14][15][16][17][18][19]. A route to selecting substrate alloys and bond coat alloys for environmental coatings for metallic UHTMs was discussed in [2] and the design of bond coat alloys that form the α-Al 2 O 3 scale was discussed in [15,16].…”
Section: Introductionmentioning
confidence: 99%